Proceedings of the Second Workshop on Building Educational Applications Using NLP - EdAppsNLP 05 2005
DOI: 10.3115/1609829.1609839
|View full text |Cite
|
Sign up to set email alerts
|

Measuring non-native speakers' proficiency of English by using a test with automatically-generated fill-in-the-blank questions

Abstract: This paper proposes the automatic generation of Fill-in-the-Blank Questions (FBQs) together with testing based on Item Response Theory (IRT) to measure English proficiency. First, the proposal generates an FBQ from a given sentence in English. The position of a blank in the sentence is determined, and the word at that position is considered as the correct choice. The candidates for incorrect choices for the blank are hypothesized through a thesaurus. Then, each of the candidates is verified by using the Web. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 15 publications
0
65
0
Order By: Relevance
“…Previous work on exercise item generation has adopted different strategies for carrier sentence selection. In some cases, sentences are mainly required to contain a lexical item or a linguistic pattern that constitutes the target of the exercise, but context dependence is not explicitly addressed (Sumita et al, 2005;Arregik, 2011). Another alternative has been using dictionary examples as carrier sentences, e.g.…”
Section: Background 21 Corpus Examples Combined With Nlp For Languagmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on exercise item generation has adopted different strategies for carrier sentence selection. In some cases, sentences are mainly required to contain a lexical item or a linguistic pattern that constitutes the target of the exercise, but context dependence is not explicitly addressed (Sumita et al, 2005;Arregik, 2011). Another alternative has been using dictionary examples as carrier sentences, e.g.…”
Section: Background 21 Corpus Examples Combined With Nlp For Languagmentioning
confidence: 99%
“…Such sentences are also known as seed sentences (Sumita et al, 2005) or carrier sentences (Smith et al, 2010) in the Intelligent ComputerAssisted Language Learning (ICALL) literature. Interest for the use of corpora in language learning has arisen already in the 1980s, since the increasing amount of digital text available enables learning through authentic language use (O'Keeffe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…) with little attention given to the semantics and educational relevance of the questions (Heilman and Smith [2009], Mitkov et al [2006], Mostow and Chen [2009], Wolfe et al [1975], Wyse and Piwek [2009]). On the other hand, previous works in GFQG have generally worked with vocabularytesting and language learning (Smith et al [2010], Sumita et al [2005]). Smith et al presented TedClogg which took gap-phrases as input and found multiple choice distractors from a distributional thesaurus.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore it cannot be used with carrier sentences that do not contain strong collocations, such as the sentence in Figure 1. Sumita et al (2005) apply a simple web search approach to judge the reliability of an item. They check whether the carrier sentence with the target word replaced by the distractor can be found on the web.…”
Section: Reliability Checkingmentioning
confidence: 99%